Jurnalis Perempuan Gaza: Potret Ibu Keluarga, Pewarta Media dan Warga Negara - Musrifah (EQUALITY: Journal of Gender, Child, and Humanity Studies, 2025)
This article aims to describe the complex role of Gaza women journalists who are on the frontline of the conflict, serving three roles at once: as mothers, journalists and citizens. As mothers, they struggle to protect their children amidst the violence that continues to threaten them. As journalists, they carry the professional responsibility to voice the truth and convey the reality of war that is often ignored by the world. As Palestinian citizens, they defend their rights to their homeland and collective identity. These three roles not only intersect, but also strengthen each other in a humanitarian struggle that touches personal, professional and national aspects. Using a gender perspective and literature study method, the researcher explored media news and found that Gazan women journalists do not experience gender discrimination and cover conflict areas like male journalists. However, female journalists experience dilemmas and higher mental burdens carrying out three roles at once as mothers, journalists, and citizens.